Prevalence and factors associated to disclosure of same-sex practices to family members and health care workers among men who have sex with men in Togo. Issue 8 (3rd August 2019) - Ruiseñor-Escudero, Horacio; Lyons, Carrie; Ketende, Sosthenes; Pitche, Vincent; Simplice, Anato; Tchalla, Jules; Sodji, Dometo; Kapesa, Laurent; Baral, Stefan
ABSTRACT: Disclosure of same-sex practices is associated with improved access to health services and better health outcomes. Our aim was to estimate the prevalence of same-sex practice disclosure to family members and health care workers (HCW) in two cities in Togo. 683 MSM ≥18 years of age were surveyed using respondent driven sampling (RDS) for a cross-sectional survey using a structured questionnaire in Lomé (354 (51.8%)) and Kara ( n  = 329 (48.2%)). Median age was lower in Lomé than in Kara. A significantly higher proportion of MSM in Lomé (RDSa: 37.0%; 95% CI: 29.7, 44.3) than in Kara (RDSa: 8.0%; 95% CI: 4.7, 11.3) told a HCW that they have sex with men. Disclosure to a family member was associated with female gender, living with HIV, difficulties accessing health services, and blackmail. Disclosure to a HCW was associated with living with HIV, and physical abuse. MSM had decreased odds of disclosure to a HCW if they were living in Kara, reported female gender or intersex, or if had difficulties accessing health services. These data highlight the positive health outcomes associated with disclosure contextualized by the complex environments in which disclosure of same-sex practices takes place.